Habilidades sociais e solidariedade intergeracional no relacionamento entre pais idosos e filhos adultos - Braz, Ana Carolina (2013)
Recent demographic changes such as decreasing fertility rates and increasing life expectancy have favored intergenerational families. In this social context we use concepts from Social Skills Psychology, which focuses on the study of social interactions and interpersonal relationships. Social Skills (SS) are social behaviors that enable Social Compentence. There are different classes of SS: Assertiveness, Conversation and social resourcefulness, Emotional expressiveness, Empathy, Self-control. Interpersonal relationships have also been studied under the theoretical model of Intergenerational Solidarity (IS), which includes six dimensions: (1) Affectual (feelings and evaluations), (2) Associative (frequency and type of contact), (3) Consensual (agreement in opinions and values), (4) Functional (support), (5) Normative (expectations about obligations and norms) and (6) Structural (opportunity for interaction, due to geographical proximity) , and usually studied in association with conflict. Given that these two theoretical fields involve the interpersonal context of human development, it is possible to assume an interface between them. More specifically, social skills may be an antecedent condition favoring intergenerational solidarity. Thus, the aim of this thesis was to evaluate a possible interface between SS and IS, as well as relationship quality (RQ) among older parents and their adult children. The sample was composed of 69 parent-children dyads, ages 60 to 85 years for parents and between 25 to 50 years for the adult children. The dyads were separated according to the gender of the participants, yielding four types of dyads: Mothers and daughters (n = 17), Mothers and sons (n = 18), Fathers and daughters (n = 17), Fathers and sons (n = 18). Instruments were: IHSI - Del - Prette, IHS-Del-Prette, Scale of Intergenerational Solidarity, WHOQOL-OLD and Criterion Brazil. Descriptive and inferential analyses were performed. Initially, an analysis was performed by judges: experts evaluated the possible semantic relations between items of the IS and SS. Subsequently, correlational analyses were performed for SS, IS, sociodemographic variables and Relationship Quality. In these analyses we found evidence of association among these variables. From this evidence, models were developed through structural equation models for dyadic analysis using the Actor -Partner Interdependence Model with two predictors (at a significance level of p < 0.05, with effect size - D Cohen equal to 0.15 and the statistical power of 0.80). SS classes were found to be predictors of dimensions of IS and Conflict in intra and intergenerational analyses. We discuss the implications of these findings for research, evaluation, intervention, training of health professionals, public policies and social programs.